Four domains of p300 each bind tightly to a sequence spanning both transactivation subdomains of p53 - Teufel, Daniel P. (National Academy of Sciences, 2007)
The transcriptional coactivator p300 binds to and mediates the transcriptional functions of the tetrameric tumor suppressor p53. Both proteins consist of independently folded domains linked by intrinsically disordered sequences. A well studied short sequence of the p53 transactivation domain, p53(15–29), binds weakly to four folded domains of p300 [Taz1/cysteine–histidine-rich region 1 (CH1), Kix, Taz2/CH3, IBiD], with dissociation constants (K(D)) in the 100 μM region. However, we found that a longer N-terminal transactivation domain construct p53(1–57) bound tightly to each p300 domain. Taz2/CH3 had the greatest affinity (K(D) = 27 nM) and competes with the N-terminal domain of Mdm2 for the p53 N terminus. p300 thus can protect the N terminus of p53 against the binding of other proteins. Mutations of p53 that abrogate transactivation (L22Q/W23S, W53Q/F54S) greatly weakened binding to each p300 domain, linking phenotypic defects to weakened coactivator binding. We propose a complex between tetrameric p53 and p300 in which four domains of p300 wrap around the four transactivation domains of p53.